The Influence Of Service Quality, Price, And Promotion On Customer Satisfaction At Dewy Laundry Batam - Harianja, Josepin; Tamba , Imelda (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2025)
Abstract This study aims to determine the effect of service quality, price and promotion on customer satisfaction at Dewy Laundry Batam. This study also aims to analyze the most dominant factors influencing customer satisfaction at Dewy Landry Batam Batam. The population used in this study were regular customers of Dewy Landry Batam. The sample in this study was 100 respondents and the sampling technique used was the saturated sampling technique, namely the sampling technique when all members of the population are used as samples. The results of the study were obtained as follows: there is a positive and significant influence of service quality on customer satisfaction, there is a positive and significant influence of price on customer satisfaction, there is a positive and significant influence of promotion on customer satisfaction at Dewy Laundry Batam. Based on the beta value, it is known that the variable that has a dominant influence on customer satisfaction (Y) is the price variable (X2) with a beta value of 0.516 (51.6%).